Amalan hisbah kendiri dalam pendidikan Islam: Kajian terhadap murid-murid sekolah menengah di Kedah - Makhsin, Mardzelah; Ilias, Mohamad Fadhli; Che Noh, Mohd. Aderi (Universiti Malaya, 2014)
Hisbah is a surveillance system involving the internal control process to ensure al-amr bi al-ma'rufwa al-nahyan al-munkar implemented in Islamic Education.The main purpose of this article is to examine the determinants of self-hisbah practices through Islamic Education among secondary school students in the state of Kedah. The study involved a survey of 1785 randomly selected secondary school students from secondary schools, special model school, religious secondary schools, boarding schools, government religious schools, vocational and technical schools.The method used is a survey using questionnaires.The pilot study conducted showed the reliability of the questionnaire was at a high level (> .90).The analysis involves exploratory factor analysis (EFA) to identify the factors determining self-hisbah among students.The results of factor analysis explained the components of the self-hisbah consist of six components, namely musyaratah (promise of the heart), muraqabah (behavioral observation), muhasabah (reflection practice), muaqabah (spiritual reinforcement), mujahadah (struggle of desires) and muatabah (purification of the soul).The results of this study showed that self-hisbah contributed to the realization of the National Education Philosophy to produce a generation of students who are righteous, knowledgeable, competent, honorable and contribute to a universal civilization.